2015
DOI: 10.1590/1981-6723.4014
|View full text |Cite
|
Sign up to set email alerts
|

Nota Científica: Caracterização físico-química do óleo de abacate extraído por centrifugação e dos subprodutos do processamento

Abstract: ResumoO abacate é originário da América e considerado uma das plantas mais produtivas por unidade de área cultivada. Frutas com altos níveis de lipídios podem ser matéria-prima importante para a extração de óleo com substâncias bioativas que podem reduzir o risco de doenças. Este trabalho teve como objetivo a extração de óleo de abacate utilizando processo mecânico, semelhante ao empregado no azeite de oliva. À polpa triturada foi adicionada água numa proporção de 1:1, e a mistura foi mantida durante 40-60 min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 4 publications
0
2
0
4
Order By: Relevance
“…The revaluation of wastes from different industries has become one of the main economic approaches for zero-wastes industrial activity [4][5][6]. Few studies can be found regarding the use of these residues, and they have mainly focused on obtaining phytochemical compounds [7], oils [8], natural dyes [3], bacterial culture media [9] and starch [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The revaluation of wastes from different industries has become one of the main economic approaches for zero-wastes industrial activity [4][5][6]. Few studies can be found regarding the use of these residues, and they have mainly focused on obtaining phytochemical compounds [7], oils [8], natural dyes [3], bacterial culture media [9] and starch [10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The physicochemical parameters are important for determining aspects of biological applications and are presented in Table 1. In a study conducted by Ferrari (2015) evaluating the oil refraction index of P. americana seed, it verified a variation of 1.4620 to 1.4625 nD 25°. In another analysis by Jorge (2014) of the pulp oil of this species, 1.4615 nD 25°.…”
Section: Phytochemical Parameters and Phytochemical Screeningmentioning
confidence: 92%
“…Em comparação, a azeitona, que dá origem ao azeite de oliva, apresenta quantidades de 14% em frutos colhidos ainda verdes e de 18 a 25% nos que atingiram o estado de maturação (Whiley et al, 2002). Ferrari (2015) afirmou que "a extração do óleo de abacate a partir de frutos da variedade Hass utilizando o processo de obtenção de azeite de oliva adaptado é possível e ambos podem ser produzidos na mesma instalação industrial", o que possibilita o fornecimento de mais produtos com necessidade de baixo investimento.…”
Section: óLeo De Abacateunclassified